Phytoremediation of iron in ex-sand mining waters by water hyacinth (Eichhornia crassipes) - Qadar Hasani; NIKEN T.M. PRATIWI; YUSLI WARDIATNO; HEFNI EFFENDI; ARTHO NUGRAHA MARTIN; PURNA PIRDAUS; WAGIRAN WAGIRAN (Biodiversitas Journal of Biological Diversity, 2021)
Hasani Q, Pratiwi NTM, Wardiatno Y, Effendi H, Martin AN, Efendi E, Pirdaus P. 2020. Phytoremediation of Iron (Fe) in Ex-sand Mining Waters by Water Hyacinth (Eichhornia crassipes (Mart.) Solms). The high concentration of iron (Fe) has allegedly caused the water quality of puddles at sand mining area. The poor water quality, in which high contentrations of iron will to a reduction in aquaculture production. This study verified the ability of water hyacinths (Eichhornia crassipes (Mart.) Solms.)) as a phytoremediation agent for iron (Fe) concentration in water at the sand mining area, in East Lampung Regency, Indonesia. The study was carried out with 3 treatments and 3 replication each, including the treatment of (i) 25% water surface coverage, (ii) 50% water surface coverage, and (iii) 75% water surface coverage of water hyacinth. Measurement of Fe concentrations, bioconcentration factor (BCF) and translocation factor (TF) once a week, until Fe concentrations in water are adequate for aquaculture. This was achieved for 21 days. The results showed that the highest percentage reduction of Fe (97.49%) was observed at water hyacinth cover area 50%. The highest value of BCF was 2385.51, while the highest TF was 1.14 in stems and 1.02 in leaves. The results of this study open up opportunities for use water in ex-sand mining areas for aquaculture by the community and its management by the Government of East Lampung Regency, Lampung, Indonesia.